METODE TAHSIN DAN TAHFIDZ AL-QUR’AN DI PONDOK PESANTREN SMP MBS BUMIAYU - M. Utsman Arif Fathah (Jurnal Ilmiah Ilmu Ushuluddin, 2021)
The factor that can determine success in memorizing the Qur'an is the use of methods in memorizing, a good method can have a positive influence on memorizing the Qur'an. Among the methods that can help in memorizing are the Tahsin and Tahfidz methods. The focus of the study is the method used by the MBS Bumiayu Islamic Boarding School in fostering its students in Tahsin and Tahfidz Al-Qur'an. The research was conducted with a qualitative approach, and data collection by interview, documentation and observation techniques. The results of the study found that MBS Bumiayu used several methods in fostering its students in following Tahsin and tahfizd of the Qur'an, namely by reading listening to the ustadz reading verse by verse to be memorized and dividing it into several parts and reading it repeatedly so that it was memorized (juz' i), deposit or listen to the newly memorized memorization to the ustadz (talaqqi) and deposit it into three parts, namely sabqi (new memorization), sabaq (repeated new memorization) and manzi (old memorization), and the other memorization process is by murajaah ( repeating) memorization that has been memorized in order to prevent the loss of memorization and strengthen the memorization that has been memorized so that it becomes mutqien. As a step that makes it easier to memorize is Tahsin the Qur'an, so that students can read the Qur'an according to their makhraj and tajwid and fluently read the Qur'an